Adam and Eve in seventeenth-century thought - Almond, Philip C. (Cambridge University Press, 1999)
This book offers a fascinating account of the central myth of Western culture - the story of Adam and Eve in the Garden of Eden. Philip Almond examines the way in which the gaps, hints and illusions within this biblical story were filled out in seventeenth-century English thought. At this time, the Bible formed a fundamental basis for studies in all subjects, and influenced greatly the way that people understood the world. Drawing extensively on primary sources he covers subjects as diverse as theology, history, philosophy, botany, language, anthropology, geology, vegetarianism, and women. He demonstrates the way in which the story of Adam and Eve was the fulcrum around which moved lively discussions on topics such as the place and nature of Paradise, the date of creation, the nature of Adamic language, the origins of the American Indians, agrarian communism, and the necessity and meaning of love, labour and marriage.